The first human report of mobile colistin resistance gene, mcr-1, in Finland - Gröndahl-Yli-Hannuksela K; Lönnqvist E; Kallonen T; Lindholm L; Jalava J; Rantakokko-Jalava K; Vuopio J (WILEY, 2022)
Colistin resistance mediated by mobile mcr-1 gene has raised concern during the last years. After steep increase in mcr-1 reports, other mcr-gene variants (mcr-2 to mcr-5) have been revealed as well. In 2016, a clinical study was conducted on asymptomatic stool carriage of extended spectrum beta-lactamase (ESBL) producing Escherichia coli and Klebsiella pneumoniae among Finnish adults. All suspected ESBL producing bacterial isolates were first tested by phenotypic ESBL-confirmation methods, and then further analyzed with whole genome sequencing to identify the resistance genes. We found one study subject carrying a colistin resistant E.coli with a transferrable mcr-1 gene. This multi-drug resistant isolate, although initially suspected to be an ESBL producer, did not carry any ESBL genes, but was proven to carry several other resistance genes by using whole genome sequencing. Sequence type was ST93. The mcr-1 gene was connected to IncX4 plasmid which suggests that the colistin resistance gene locates in the respective plasmid. Here, we report the finding of a mcr-1 harboring human E.coli isolate from Finland. Clinical antimicrobial resistance (AMR) rates are low in Finland, and mobile colistin resistance has not been reported previously. This highlights the importance of AMR surveillance also in populations with low levels of resistance.